Towards sustainable consumption: the practices of Krakow students - Iwaszczuk, Aleksander; Sabal, Maciej; Iwaszczuk, Natalia (Przedsiębiorczość - Edukacja, 2025)
The article presents the results of a survey of students at two Kraków universities concerning knowl- edge related to food production and consumer behaviour practices. Its purpose is to identify such knowledge in the context of sustainability. Sustainability has become increasingly popular in recent years, both in the context of consumer attitudes and entrepreneurial strategies, taking into account the growing awareness in terms of the products and services being offered, the authors focused on a research issue considering the process of food production and public awareness of the consequences (environmental, climate) associated with it. Students were selected for research who, as consumers and future opinion leaders, will determine the market practices of producers. In addition, the article assesses the impact of academia (universities) on economic and social sustainability.